CRIMINAL LIABILITY OF ILLEGAL CIGARETTE SMUGGLERS IN PEMATANGSIANTAR: Study of Decision No. 213/Pid.B/2023/PN Pms - Simbolon, Krisna Uli; Sihotang, Lesson; Gultom, Meli (jfpublisher, 2025)
Illegal cigarette smuggling is an illegal act that results in a loss of state revenue and creates unfair economic competition. Therefore, to prevent this practice, the government has imposed an excise policy. However, in reality, this effort has not been able to fully suppress the smuggling of illegal cigarettes. This is proven by the prevalence of smuggling cases, even though the perpetrators have been subject to criminal sanctions. This research examines two main problems on how the juridical review of the sanctions implementation related to the purpose of punishment for perpetrators of the illegal cigarette smuggling crime in Decision No. 213/Pid.B/2023/PN Pms, and the judge's strategy in imposing a decision in order to create legal certainty and justice. This is a normative legal research where the results indicate that the implementation of criminal sanctions of a one year and six months prison sentence for the illegal cigarette smugglers in the case is still relatively light and has not provided a deterrent effect, both for the perpetrators and the wider community. Therefore, it is necessary to impose heavier criminal sanctions as a form of legal liability for the perpetrators. In addition, judges in making decisions must consider juridical and non-juridical aspects. It does not only focus on juridical aspects, but also needs to consider non-juridical factors in order to prevent errors and manipulation in the examination of cases and the implementation of sanctions against defendants.